Experimental characterization of the self-healing capacity of cement based materials and its effects on the material performance: A state of the art report by COST Action SARCOS WG2. (10th April 2018) - Ferrara, Liberato; Van Mullem, Tim; Alonso, Maria Cruz; Antonaci, Paola; Borg, Ruben Paul; Cuenca, Estefania; Jefferson, Anthony; Ng, Pui-Lam; Peled, Alva; Roig-Flores, Marta; Sanchez, Mercedes; Schroefl, Christof; et al.
Highlights: Review of test methods for assessing healing efficiency. Novel perspective in correlating healing to durability and mechanical recovery. Correlation between different test methods. Characterization methods of healing products. Pioneer monitored case studies are presented. Abstract: Heuristically known at least since the first half of XIX century, the self-healing capacity of cement-based materials has been receiving keen attention from the civil engineering community worldwide in the last decade. As a matter of fact, stimulating and/or engineering the aforementioned functionality via tailored addition and technologies, in order to make it more reliable in an engineering perspective, has been regarded as a viable pathway to enhance the durability of reinforced concrete structures and contribute to increase their service life. Research activities have provided enlightening contributions to understanding the mechanisms of crack self-sealing and healing and have led to the blooming of a number of self-healing stimulating and engineering technologies, whose effectiveness has been soundly proved in the laboratory and, in a few cases, also scaled up to field applications, with ongoing performance monitoring. Nonetheless, the large variety of methodologies employed to assess the effectiveness of the developed self-healing technologies makes it necessary to provide a unified, if not standardized, framework for the validation and comparative evaluation of the same self-healing technologies as above. This is also instrumental to pave the way towards a consistent incorporation of self-healing concepts into structural design and life cycles analysis codified approaches, which can only promote the diffusion of feasible and reliable self-healing technologies into the construction market. In this framework the Working Group 2 of the COST Action CA 15202 "Self-healing as preventive repair of concrete structures – SARCOS" has undertaken the ambitious task reported in this paper. As a matter of fact this state of the art provides a comprehensive and critical review of the experimental methods and techniques, which have been employed to characterize and quantify the self-sealing and/or self-healing capacity of cement-based materials, as well as the effectiveness of the different self-sealing and/or self-healing engineering techniques, together with the methods for the analysis of the chemical composition and intrinsic nature of the self-healing products. The review will also address the correlation, which can be established between crack closure and the recovery of physical/mechanical properties, as measured by means of the different reviewed tests.